The necessity and challenges of human papillomavirus testing for men - Ren, Wenbo; Jin, Yuting; Shi, Lin; Chen, Haizhen; Zhang, Zichen; Wang, Yifei; Zhai, Taiyu; Huang, Jing (Frontiers in Cellular and Infection Microbiology, 2025)
Beyond its historical association with cervical cancer in women, human papillomavirus (HPV) infection poses a widespread health concern, particularly for men. Recent studies have highlighted the prevalence of HPV-related cancers, including penile and anal cancers, among the male population, making the case for male HPV testing all the more compelling. The potential for cross-infection between sexual partners underscores the need for comprehensive screening strategies. However, challenges still remain, such as the limited availability of testing methods and the absence of uniform medical guidelines, hampering effective HPV detection in men. Addressing these challenges through intensified research efforts and the revision of medical guidelines is crucial to enhancing prevention strategies and unlocking significant public health benefits.